The horticultural improvement of city lots - Waugh, Frank Albert (My University, 1891)
Introduction: Landscape gardening is not as many people suppose, and ultra-practical fine art. Both as an art and as a science it is as applicable to the needs of everyday life as its nearest relative, architecture or as horticulture itself. The designing and care of large city packs has been recognized as professional work but short of such undertakings any farmer or lawyer believes himself able to plan a cemetery, a school yard or the planting about his own house. And he believes that any day laborer about turn is able to do the work after that. He is usually as much mistaken in the one as in the other. There is not time here to preface a proper review of the methods in common practice, nor to nurture fairly the field of possible improvements. We will confine ourselves, for the present discussion, strictly to city residence lots and consider briefly their arrangements of the light of ordinary principles of harmony and good taste.
Citation: Waugh, Frank Albert. The horticultural improvement of city lots. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Horticulture; Landscape; Gardening; Nature; Botany; City lots; Theses; Manuscripts (documents)